Effect of Pulsed Electric Field Pre-Treatment on Chemical Composition and Antioxidant Properties of Apricots Dried Using Conventional Air Drying and Freeze Drying Methods - Mani, Shyamkrishna (Auckland University of Technology, 2019)
Apricots are temperate zone fruits and are largely produced in the Mediterranean region. They are favoured by the general population for their sweet taste and health benefits. The compounds present in apricots are said to have antioxidant properties that are proven to have health benefits. Pulsed electric field is a non-thermal food preservation technology that retains nutritional value and food quality attributes. Recently, pulse electric field has been used as a pre-treatment prior to drying and has been found to significantly reduce the drying time making that increase drying efficiency. The objective of this study was to examine the change in chemical composition of apricots after pulsed electric field processing at different pulse intensity levels of 0.7 kV/cm (low), 1.2 kV/cm (medium) and 1.8 kV/cm (high), and also no pulsed electric field treatment (control) followed by the process of drying. The treated apricots were either air dried (70 ℃ for 12 hours) or freeze dried. The changes in organic acids, free fatty acids, free amino acids and antioxidant capacity in the apricot samples were observed using various methods. PEF and drying methods on the apricot sample significantly increased the concentration of individual organic acids at different intensities of pulsed electric fields. In air dried samples of apricots, fumaric, malic, oxalic and shikimic acid, isocitric, succinic, benzoic, citric and oxaloacetic acids in the air dried samples were significantly higher with the different pulsed electric field pre-treatments at different intensities. In the freeze dried apricot samples, fumaric, succinic and isocitric acids, malic, shikimic, citric and oxaloacetic acids were significantly higher in the pulsed electric field treated samples. The free fatty acid content in the pulsed electric field treated air dried and freeze dried apricots were significantly different in terms of octanoic, myristic, pentadecanoic, palmitic, margaric, linoleic, stearic, octadecatrieonic and arachidic acids. The free amino acid content in pulsed electric field treated air dried and freeze dried apricot samples also showed a significant difference in concentrations of individual free amino acids ( alanine, glycine, 2- aminobutyric acid, valine, threonine, leucine, norleucine, aspartic acid, 4-aminobutyric acid, proline, theonine, S-adenosvlmethionine, asparagine, serine, trans-4-hydroxyproline, glutathione, cis-4-hydroxyproline, phenylalanine, lysine, histidine, tyrosine, delta- hydroxylysine, tryptophan and L-isoleucine). The antioxidant content of the apricots were affected by pulsed electric field treatment in the cupric ion reducing antioxidant capacity assay and the ferric reducing ability of plasma assay. In the cupric ion reducing antioxidant assay, there was a significant difference in the antioxidant content of air dried apricot samples treated at different pulsed electric field intensities. The low and medium intensity pulsed electric field treatments resulted in significantly higher antioxidant activities compared to control samples. In the freeze dried samples, with varying PEF intensities, the control samples had significantly higher antioxidant capcity compared to the pulse electric field treated samples. With the ferric reducing ability of plasma assay, a significant increase in antioxidant activity was found with increase in pulsed electric field intensity in the air dried samples. However, there was no significant difference in the concentration of antioxidant activity in the freeze dried samples at different intensities of pulsed electric field treatment. In addition, freeze dried apricots had significantly higher antioxidant capacities (p < 0.05) compared to air dried apricots. Total polyphenol content of air dried pulsed electric field treated samples were significantly higher than control air dried samples. However, for freeze dried samples, there was no significant increase between the control and pulsed electric field treated freeze dried samples. In general, the treatment methods displayed a significant increase in essential nutritional composition of dried apricots and hence PEF can be an important treatment method to increase the nutritive content of dried apricots compared to the non-PEF treated dried apricots that are available in the market.
Keywords: Apricots; PEF; Air drying; Freeze drying; Chemical composition; Antioxidants